Surgical Treatment of Sublingual Gland Ranulas - Gontarz, Michał; Bargiel, Jakub; Gąsiorowski, Krzysztof; Marecik, Tomasz; Szczurowski, Paweł; Zapała, Jan; Gałązka, Krystyna; Wyszyńska-Pawelec, Grażyna (International Archives of Otorhinolaryngology, 2022)
Introduction Ranulas are divided into oral (OR) and plunging (PR) and comprise the most common pathology of the sublingual gland. This study presents a case series of patients operated due to OR and PR within different type of modalities in a 1-year period.Objective The aim of this study is to determine the optimal surgical treatment of ranulas based on our results as well as in the literature review.Methods The medical charts of 7 patients with sublingual gland ranulas treated in 2020 were reviewed.Results The median age of the patients was 19. Three patients with OR were treated by marsupialization, micromarsupialization, and sublingual gland excision. Four patients with PR were operated via cervical approach in three cases and intraoral approach in one case. No recurrence was observed in 14 months of follow-up, on average.Conclusion Micromarsupialization should be consider as the primary treatment for OR. In case of recurrent OR and primary or recurrent PR, the best results might be obtained by radical excision of the sublingual gland, which can be performed without resection of the ranula sac with the intraoral approach.
Keywords: ranula; oral ranula; plunging ranula; salivary gland; sublingual gland; treatment